Recent update in diagnosis and treatment of human pythiosis - Chitasombat,Maria Nina; Jongkhajornpong,Passara; Lekhanont,Kaevalin; Krajaejun,Theerapong (PeerJ, 2020)
Human pythiosis is an infectious condition with high morbidity and mortality. The causative agent is the oomycete microorganism Pythium insidiosum. The pathogen inhabits ubiquitously in a wet environment, and direct exposure to the pathogen initiates the infection. Most patients with pythiosis require surgical removal of the affected organ, and many patients die from the disease. Awareness of pythiosis among healthcare personnel is increasing. In this review, we summarized and updated information on the diagnosis and treatment of human pythiosis. Vascular and ocular pythiosis are common clinical manifestations. Recognition of the typical clinical features of pythiosis is essential for early diagnosis. The definitive diagnosis of the disease requires laboratory testing, such as microbiological, serological, molecular, and proteomic assays. In vascular pythiosis, surgical intervention to achieve the organism-free margin of the affected tissue, in combination with the use of antifungal drugs and P. insidiosum immunotherapy, remains the recommended treatment. Ocular pythiosis is a serious condition and earliest therapeutic penetrating keratoplasty with wide surgical margin is the mainstay treatment. Thorough clinical assessment is essential in all patients to evaluate the treatment response and detect an early sign of the disease recurrence. In conclusion, early diagnosis and proper management are the keys to an optimal outcome of the patients with pythiosis.
Keywords: Pythium insidiosum; Pythiosis; Diagnosis; Treatment; Management